Determinación del costo de venta del huevo semicriollo de la red de mujeres del Departamento de Casanare (2021)
The present work establishes the feasibility of implementing a standard costing system, to calculate the real projected value of the semi-chicken egg for unit, helping and contributing all our knowledge to the network of women of Yopal – Casanare to this end, takin0g into account that this project of the aforementioned group of women, helps economic, social and productive development, economic because they generate income and improve their quality of life, social because they generate employment for people who do not have a fixed and productive livelihood because they encourage more people to undertake, developing more project like this. In the research to start this work, two very important aspects were taken into account, such as everything related to the poultry sector this aspect includes, the storage of chickens, the illnesses that they can contract both themselves and the human resource that manipulate them, the second aspect was to keep in mind everything related to standard costs, identifying the elements that compose it (direct labor, direct raw material and indirect manufacturing costs), to stipulate the project value that is required. During the research process and to clarify the two aspects, several tools were used which were very important to reach the final result, which was the projected value of the semi-chicken egg for unit, we spoke with the leader of the group of women, a limited photographic record thanks to the current health situation and the knowledge to develop the standard cost system